Current Trends in Writing Thesis at Master’s Level in English of Humanities and Social Sciences - Gurung, Raj Kumar; Thapa, Hukum (Khwopa Journal, 2023)
This paper explores the current trends in writing thesis in M. A. English. Both the supervisors and master’s level students encounter several problems during the thesis writing process. Most of the students do not update the MLA and APA formats and other components of thesis. Then some students purchase the readymade thesis from the market or hire the ghost writers. This study analyzes the problems faced by the thesis supervisors and the students. Thesis writing has been a challenging job for the students because of various contexts and issues. It intends to generate some concrete suggestions to settle the issues of thesis supervising and writing by investigating and identifying the genuine problems. The current trend of thesis writing is not satisfactory. This paper aims to create the friendly environment between the supervisors and thesis writing students so that thesis writing process becomes simpler. The study adopts the survey methods and document analysis for the discussion of the issues raised. This project focuses on these questions: Why has thesis writing become the most challenging task? Who is responsible, the supervisors or students? What are the ways of making thesis supervising and writing friendlier? This study aims to bridge the gap between supervisors and the students; and open the avenue for the further research to bring out result oriented and less problematic thesis